Pemenuhan Nafkah Keluarga dengan Suami Gangguan Mental Perspektif Iṡtisna’iyat At-Taklif - Devi, Elvira Rahma; Nashirudin, Muh (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2024)
This study explores the fulfillment of family needs in two households in the village of Mendak, where the husbands suffer from mental disorders and the wives have to earn a living. The study also discusses the concept of Iṡtisna’iyat At-Taklif, which exempts individuals with mental disorders from legal obligations. This field research involved interviews with these wives, neighbours, and village officials, as well as related literature studies. The results show that the wives of men with mental disorders must work to meet their family's needs, with assistance from family, neighbours, and the village government. In terms of legal capability, the husbands in this study have fluctuating legal competence depending on their conditions. These cases fall under the